The role of ettringite in the deterioration of artificial lime stabilised soils: a microstructural study - Buttress, A.J.; Grenfell, J.R.A.; Airey, Gordon (Taylor & Francis, 2013)
The formation of ettringite has been defined as a major failure mechanism of lime stabilised cohesive soils. It can result in both disruptive volumetric changes and loss of mechanical strength. The mechanisms of its formation and the role it plays in deleterious processes are complex. This paper reports the dimensional and strength changes of a range of artificial lime stabilised cohesive soils subject to two swell test procedures: the UK linear CBR swell test (BS1924-2, BSI 1990) and the European accelerated swell test (EN13286-49, CEN 2007). The resulting microstructural composition was analysed using a combination of Scanning Electron Microscopy and Electron Dispersive X-ray Spectroscopy (SEM-EDX). The results are explained in terms of established theories of crystal formation and subsequent expansion mechanisms.